An Exploration of the Impact of Anti‐TNFα Medication on Exercise Behaviour in Patients with Ankylosing Spondylitis. (19th February 2014) - Stockdale, Jennifer; Selfe, James; Roddam, Hazel
Abstract Background Exercise has traditionally been an important part of the treatment of ankylosing spondylitis (AS) in order to maintain spinal mobility. Additionally, anti‐tumour necrosis factor‐alpha (TNFα) medication has been proven highly effective in treating the condition. Over recent years, a few papers have shown the synergistic effect of combining anti‐TNFα medication with rehabilitation. There is minimal evidence on the perceptions of AS patients on how the medication has affected their exercise behaviour. The aim of the present study was to explore the effects of anti‐TNFα medication on exercise behaviour in patients with AS. Method A qualitative approach was adopted to provide a holistic understanding of participants' exercise behaviour while on anti‐TNFα medication. Semi‐structured interviews were undertaken and transcribed verbatim. Data were analysed using thematic network analysis. Ethical approval and informed consent were obtained. Results Twenty participants (age range 26–74, disease duration 3–36 years) who had been on the medication for over a year described how their exercise behaviour had improved since being on the medication. They highlighted their motivation and incentives to continue with an exercise programme. The participants had reinstated previous sporting activities, started new ones and regularly undertook physiotherapy exercises. Conclusion The present study provides evidence of the long‐term effects of anti‐TNFα medication on the exercise behaviour of AS patients. It shows that AS patients are able to sustain a regular exercise programme over a number of years, provides insight into what motivates them to exercise and reveals the incentives that have influenced their choice of activity. Copyright © 2014 John Wiley & Sons, Ltd.